Environmental DNA metabarcoding as an effective and rapid tool for fish monitoring in canals - Allan D. McDevitt; Naiara Guimarães Sales; Samuel S. Browett; Abbie O. Sparnenn; Stefano Mariani; Owen S. Wangensteen; Ilaria Coscia; Chiara Benvenuto (Journal of Fish Biology, 2019)
We focus on a case study along an English canal comparing environmental DNA (eDNA) metabarcoding with two types of electrofishing techniques (wade‐and‐reach and boom‐boat). In addition to corroborating data obtained by electrofishing, eDNA provided a wider snapshot of fish assemblages. Given the semi‐lotic nature of canals, we encourage the use of eDNA as a fast and cost‐effective tool to detect and monitor whole fish communities.